Evaluation of Application of Principles Good Governance in Public Services in Jekan Raya District, Palangka Raya City - Andriani; Rulandari, Novianita (Indonesian Scientific Publication, 2024)
Efficient and effective bureaucratic services are essential in creating community welfare and are the main indicators of success in implementing good governance. Regional governments have a vital role in ensuring the principles of good governance to meet community expectations for transparent, accountable, and fair services. This research aims to evaluate the application of the principles of good governance in Jekan Raya District, Palangka Raya City, which is facing challenges in managing public resources and services, including increasing community demands and the need for transparency in budget management. Using a qualitative approach through the case study method, this research analyzes the obstacles, challenges, and strategies needed to increase the effectiveness of exemplary governance implementation. The research results show that although Jekan Raya District has great potential to support development, there are various problems in the implementation of good governance, such as a lack of community participation, limited facilities, and ineffective bureaucratic structures. Therefore, increasing communication between the government and the community, updating facilities, and increasing employee discipline is necessary to improve public service quality. This research provides theoretical and practical contributions to the development of governance at the local level, especially in the Jekan Raya District, as a step towards better and more sustainable regional development.